2002
DOI: 10.2320/matertrans.43.2860
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Thermally Sprayed WC Coating in Na<SUB>2</SUB>SO<SUB>4</SUB> Aqueous Solution

Abstract: WC-Co thermally sprayed coating, formed by high velocity oxygen-fuel flame spraying, has had the problem of low corrosion resistance in aqueous solutions. Furthermore, much remains unknown regarding corrosion reactions on coating surfaces and the formation of passivation films. This study focused on changes of the corrosion surfaces of two thermally sprayed coatings, WC-12Co and WC-10Co-4Cr, with immersion time. The chemical composition of the corrosion surfaces was analyzed by electron spectroscopy, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This is confirmed by analysis of corrosion and, as reported in previous paper [21,23,27,28], corrosion initiates at the carbide/metal interfaces where it would appear the film integrity is lowest. It has also been reported that the formation of Cr 2 O 3 in WC-based coatings takes place as small islands spread non-uniformly over the surface [32]. Table 2 shows the corrosion current density values measured under erosion-corrosion conditions and it is clear that the impinging liquid-solid stream significantly increases the corrosion rate compared to static conditions.…”
Section: Corrosion Characteristicsmentioning
confidence: 88%
“…This is confirmed by analysis of corrosion and, as reported in previous paper [21,23,27,28], corrosion initiates at the carbide/metal interfaces where it would appear the film integrity is lowest. It has also been reported that the formation of Cr 2 O 3 in WC-based coatings takes place as small islands spread non-uniformly over the surface [32]. Table 2 shows the corrosion current density values measured under erosion-corrosion conditions and it is clear that the impinging liquid-solid stream significantly increases the corrosion rate compared to static conditions.…”
Section: Corrosion Characteristicsmentioning
confidence: 88%
“…Negative synergies have not been reported previously for the WC-10Co-4Cr coatings and therefore this is potentially a significant new insight. The negative synergy may be influenced by the formation discontinuous passive film [28,33] and/or localised corrosion along the periphery of the carbide grains ( Fig. 9b and d).…”
Section: Micro-abrasion and Wear-corrosion Synergymentioning
confidence: 96%
“…The electrochemical behaviour of UNS S31603 stainless steel was compared with a HVOF WC-10Co-4Cr coating and it was observed that unlike the continuous passive film of Cr 2 O 3 present on the stainless steel, only the CoCr matrix in the HVOF coating passivated and developed a thick Cr 2 O 3 film in a 3.5% NaCl solution. Also, Takeda et al [33] observed a Cr 2 O 3 passive film on a WC-10Co-4Cr coating after immersion in Na 2 SO 4 solution and concluded that this film did not cover the entire surface and was present in the form of islands. Discontinuity in the film is likely to coincide with the binder-carbide interface and hence corrosion is likely to be initiated at this interface when corrosive electrolytes are present [30].…”
Section: Introductionmentioning
confidence: 97%
“…This can be related to the more negative corrosion potentials, ranging from − 372 mV versus SCE (WC-10Ni) to − 414 mV versus SCE (WC-12Co). Moreover, according to Li et al, the corrosion resistance of WC-12Co can be affected by the oxidation of the Co matrix, leading to formation of non-protective oxides such as Co 3 O 4 and CoO at neutral pH, which are easily dissolved and can promote the continuous dissolution of the coating (Ref 8 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is widely reported that WC-Co and WC-Ni coatings tend to have low corrosion resistance as a result of micro-galvanic cells formed between the ceramic phase and the metal binder (Ref 15 - 18 ). Many authors have found that the formation of porous non-protective cobalt oxide (CoO) leads to low corrosion resistance of WC-Co coatings (Ref 8 , 15 , 19 ). Nevertheless, Cr 3 C 2 coatings with a matrix of NiCr and Ni tend to have high corrosion resistance in a variety of corrosive media (Ref 8 , 15 , 20 - 23 ).…”
Section: Introductionmentioning
confidence: 99%